2017
DOI: 10.1017/s1049023x17000280
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perception of Medical Students’ Knowledge and Interest in Disaster Medicine: Nine Years After the Approval of the Curriculum in German Universities

Abstract: German students are still largely not well educated regarding disaster medicine, despite their high motivation. The curriculum of 2006 was not implemented as originally planned and the number of trained students still remains low as the self-perception of knowledge. Currently, there is no clear and standardized training concept in place. A renewal in the agreement of implementation of the curriculum at medical schools should be targeted in order to follow the recommendation of WADEM. Wunderlich R Ragazzoni L I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…[23]. Although German students were highly motivated, the majority were not well educated regarding disaster medicine [22]. A study in Belgium indicated that the respondents wanted to increase their knowledge in this area and welcomed the introduction of specific courses into the standard medical curriculum [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23]. Although German students were highly motivated, the majority were not well educated regarding disaster medicine [22]. A study in Belgium indicated that the respondents wanted to increase their knowledge in this area and welcomed the introduction of specific courses into the standard medical curriculum [42].…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaire development was based on review of literature [9,18,22]. A pre-validated questionnaire was already being used in a study in Qatar [26].…”
Section: Tool Developmentmentioning
confidence: 99%
“…[ 19 ] Students generally believe in the importance of teaching disaster medicine in the regular curriculum and are generally highly motivated to learn disaster medicine. [ 20 , 21 ] A previous study also indicated that medical students could have misconceptions regarding disasters. [ 8 ] Consistent with previous studies, despite a high willingness to participate in disaster management, the students might have not been well educated regarding such situations.…”
Section: Discussionmentioning
confidence: 99%
“…Some universities teach this subject more or less, mostly in France, Germany and UK. There should however be more time for these issues and students were very motivated to learn these subjects [9]. Another survey among medical students showed that they are motivated to help during disaster situations or influenza pandemics, but also that they are not educated for disaster situations [10].…”
Section: Medical Students' Behaviour During Recent Global Threatsmentioning
confidence: 99%